Assessment of multidimensionality determinants of eye care adherence among type 2 diabetic patients in Shiraz, Iran - Zahra Sharifi; Zahra Soleimani; Seyed Moein Mahini; Mahmood Nejabat; Hossein Molavi Vardanjani (Elsevier, 2024)
Aim: This study explores the diverse factors influencing the eye care adherence of individuals diagnosed with type 2 diabetes mellitus in Shiraz. The lack of effective strategies in Iran to improve eye care behaviors and reduce retinopathy incidence in diabetes patients necessitates this research. The goal is to assess factors that affect this adherence. Method: A cross-sectional survey was conducted in Shiraz, Iran during 2022-2023. This study's primary data collection tool was an exhaustive questionnaire. This was carefully designed to include various sections, each focusing on different aspects relevant to the study's aim. Result: The study found that being female, married, literate, and overweight resulted in more annual ophthalmology visits. Possessing additional insurance and adhering to diabetic controls and care were positively correlated with ophthalmology visits. Less reliance on family income or loans led to better eye care. The shorter duration of diabetes and proximity to a diabetic care unit were crucial factors for improved eye protection. Conclusion: This study offers insights into the various factors affecting eye care utilization patterns among individuals diagnosed with type 2 diabetes mellitus in Shiraz. The study's findings underscore the significance of demographic factors in influencing individuals' engagement in self-care practices and their access to eye care services. Further research is needed to delve into the cultural and sociodemographic determinants underlying these trends, which will aid in developing treatments that cater to the diverse needs of individuals with diabetes.